1993
DOI: 10.1111/j.1528-1157.1993.tb02115.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Vigabatrin in Refractory Epilepsy: A Ceiling to Effective Dosage in Individual Patients?

Abstract: A double-blind, randomized, cross-over study of additional vigabatrin (gamma-vinyl-GABA, VGB, 1.0 g twice daily for 6 weeks, followed by 1.5 g twice daily for 6 weeks) and matched placebo was undertaken in 24 patients with refractory epilepsy. Nineteen completed the trial satisfactorily. Fewer seizure days were reported during VGB treatment [placebo 41, VGB 23, p < 0.05, 95% confidence interval (CI) -1.5 to -14]. An overall reduction in median seizure numbers failed to reach statistical significance (n = 19; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 36 publications
(34 reference statements)
0
24
0
Order By: Relevance
“…In all but four of the trials, which involved patients with both generalised and partial seizures, 54,83,85,86 all patients had partial seizures. The trials recruited between 23 and 182 (mean = 72) patients and followed them up for periods of 4-18 weeks (mean = 10 weeks).…”
Section: Figure 18 Proportion Of 50% Responders (Unpooled Rrs 95% CImentioning
confidence: 99%
See 3 more Smart Citations
“…In all but four of the trials, which involved patients with both generalised and partial seizures, 54,83,85,86 all patients had partial seizures. The trials recruited between 23 and 182 (mean = 72) patients and followed them up for periods of 4-18 weeks (mean = 10 weeks).…”
Section: Figure 18 Proportion Of 50% Responders (Unpooled Rrs 95% CImentioning
confidence: 99%
“…However, they reported the number of patients who achieved at least a 50% reduction in seizure frequency with VGB, which ranged from 33 to 67%. 49,54,83,[85][86][87] In the trial that reported the largest benefit, it was unclear if an appropriate paired analysis was performed or if patients had constant and predictable seizure frequencies. 49 That study and two others 83,85 did not report a washout period but the possible effects on the reported findings were not mentioned.…”
Section: Figure 18 Proportion Of 50% Responders (Unpooled Rrs 95% CImentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Perucca et al (1) nicely reviews the probable role of VGB in increasing seizure frequency or inducing new seizure types. An effective "therapeutic ceiling dose" has been postulated for VGB with deterioration in seizure control possible when this dosage is exceeded (25). In one series, increased numbers of seizures were clearly related to escalations in VGB dose in one-fourth of pediatric patients (26).…”
mentioning
confidence: 99%